Demographic and Clinical Features of Pediatric Uveitis in Israel. (2nd January 2020) - Habot-Wilner, Zohar; Tiosano, Liran; Sanchez, Juan M.; Shulman, Shiri; Barequet, Dana; Rahat, Ori; Amarilyo, Gil; Amer, Radgonde
ABSTRACT: Purpose : To report the epidemiology, etiology, ocular characteristics, treatment and visual outcome of pediatric uveitis in Israel. Methods : Retrospective study from two tertiary uveitis centers. Results : Included were 107 patients (182 eyes), 55% females. Mean age at diagnosis 8.8 years. Uveitis was predominantly anterior, idiopathic, bilateral, and chronic. Systemic associations were seen in 36% of patients of which the most common disease was juvenile idiopathic arthritis. Infectious uveitis accounted for 37% of posterior uveitis cases of which toxoplasmosis was the most common cause. Anterior segment complications were commonly observed at presentation (41%); the most predominant were posterior synechiae, cataract, and band keratopathy. The most common posterior segment complications were papillitis, epiretinal membrane, and macular atrophy/scar. Ninety-three percent of eyes had visual acuity >20/40 at last follow-up. Conclusion : The pattern of pediatric uveitis in Israel is similar to that in the western world. Visual outcome was good in most eyes.